مقدرات الاختبار الأولي المقلصة ذات المرحلة الواحدة لمعلمة القياس للتوزيع الأسي - سلمان, عباس نجم; خلف, بيداء عطية; حمزة, سيران (Journal of Economics and Administrative Sciences, 2010)
A preliminary test single stage Shrinkage (PTSSS) techniques is used for estimation the scale parameter q of an exponential distribution when a prior knowledge about q is a available in the form of initial estimate q0 of q. It is proposed to estimate q by a testimator  that is based upon the result of a test of the hypothesis H0 :q = q0 against the hypothesis HA :q ¹ q0 with level of significance a. If H0 is accepted we take , where the weighting factor  is a function of the test statistic for testing H0 or may be constant such that . However if H0 is rejected we take , where  and  is the classical estimator of q (MLE). Choosing the weighting factor , (i =1,2) appropriately, an expression for the mean squared error (MSE) and Bias of  are derived and comparisons are made with classical estimator () in the sense of efficiency and last earlier studies.